DNA-nanotechnology-enabled chiral plasmonics: from static to dynamic - Zhou, Chao; Duan, Xiaoyang; Liu, Na (Accounts of chemical research, 2017)
The development of DNA nanotechnology, especially the advent of DNA origami, has made DNA ideally suited to construct nanostructures with unprecedented complexity and arbitrariness. As a fully addressable platform, DNA origami can be used to organize discrete entities in space through DNA hybridization with nanometer accuracy. Among a variety of functionalized particles, metal nanoparticles such as gold nanoparticles (AuNPs) feature an important pathway to endow DNA origami -assembled nanostructures with tailored optical functionalities. When metal particles are placed in dose proximity, their particle plasmons, collective oscillations of conduction electrons, can be coupled together, giving rise to a wealth of interesting optical phenomena. Nevertheless, characterization methods that can read out the optical responses from plasmonic nanostructures composed of small metal particles, and especially can optically distinguish in situ their minute conformation changes, are very few. Circular dichroism (CD) spectroscopy has proven to be a successful means to overcome these challenges because of its high sensitivity in discrimination of three-dimensional conformation changes. In this Account, we discuss a variety of static and dynamic chiral plasmonic nanostructures enabled by DNA nanotechnology. In the category of static plasmonic systems, we first show chiral plasmonic nanostructures based on spherical AuNPs, including plasmonic helices, toroids, and tetramers. To enhance the CD responses, anisotropic gold nanorods with larger extinction coefficients are utilized to create chiral plasmonic crosses and helical superstructures. Next, we highlight the inevitable evolution from static to dynamic plasmonic systems along with the fast development of this interdisciplinary field. Several dynamic plasmonic systems are reviewed according to their working mechanisms. We first elucidate a reconfigurable plasmonic cross structure that can execute DNA-regulated conformational changes on the nanoscale. Hosted by a reconfigurable DNA origami template, the plasmonic cross can be switched between a chiral locked state and an achiral relaxed state through toehold mediated strand displacement reactions. This reconfigurable nanostructure can also be modified in response to light stimuli, leading to a noninvasive, waste-free, and all-optically controlled system. Taking one step further, we show that selective manipulations of individual structural species coexisting in one ensemble can be achieved using pH tuning of reconfigurable plasmonic nanostructures in a programmable manner. Finally, we describe an alternative to achieving dynamic plasmonic systems by driving AuNPs directly on origami. Such plasmonic walkers, inspired by the biological molecular motors in living cells, can generate dynamic CD responses when carrying out directional, progressive, and reverse nanoscale walking on DNA origami. We envision that the combination of DNA nanotechnology and plasmonics will open an avenue toward a new generation of functional plasmonic systems with tailored optical properties and useful applications, including polarization conversion devices, biomolecular sensing, surface-enhanced Raman and fluorescence spectroscopy, and diffraction-limited optics.